Pelatihan Penggunaan MIT App Inventor untuk Membuat Aplikasi Android pada Siswa di Bale Mesin Digital - Wahyu Kurniawan; Lalu Mutawalli; Wire Bagye (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
This training aims to provide training on the use of MIT App Inventor in creating Android applications to students at Bale Machine Digital. MIT App Inventor is a web-based platform that makes it easy for new users to program and create Android apps through a block-based Invalid source specified.men interface. The research methods used include problem identification, preparation, training implementation and evaluation. The results of this training show a significant increase in students' knowledge and skills in using information technology and creating Android applications. This training also provides basic skills that are much needed in today's digital era and can be the basis for developing business opportunities in the future.